Thelonious Monk Quartet with John Coltrane at Carnegie Hall - Solis, Gabriel, 1972- (Oxford studies in recorded jazz., 2013)
Thelonious Monk Quartet with John Coltrane at Carnegie Hall is an historical, cultural, and analytical study of the album by the same name. Recorded in 1957, but lost until 2005, it is a particularly interesting lens through which to view jazz both as a historical tradition and as a contemporary cultural form.